Anxiety Level of Post-Sectio Caesarea With Breast Milk Production - Ima Sukmawati; Asep Gunawan; Lena Noviana (LPPM STIKes Muhammadiyah Ciamis, 2023)
Introduction: Breastfeeding is one of the most effective ways to provide nutrition and keep babies healthy. Exclusive breastfeeding is also able to reduce infant morbidity and mortality, but currently, exclusive breastfeeding has reached the presentation stage. Milk production that is not sufficient for the baby's needs will cause the failure of exclusive breastfeeding. The psychological preparation of a mother before breastfeeding is an important factor that influences the success of breastfeeding. Mothers anxiety, stress, excessive worry, and frustration play a very important role in the success of exclusive breastfeeding. Constant anxiety, a lack of self-confidence, depression, and various other forms of emotional stress can prevent a mother from breastfeeding her baby. Objective: This study aims to determine the relationship between the anxiety level of post-sectio caesarea mothers with breast milk production at the Ciamis General Hospital. Method: The research method is quantitative with a cross-sectional research design. The sampling technique was accidental sampling, namely of post-SC mothers at the Ciamis General Hospital, namely as many as 27 people. The research instrument was a questionnaire sheet. Data analysis used univariate and bivariate analysis with the chi-square statistical test. Result: The result showed the anxiety level of post-section caesarea mothers, most of the categories of moderate anxiety were found, namely 14 people (51.9%). Nearly half of the post-SC mother's milk production was in the lower category, namely 12 people (44.4%). The statistical test results showed a p value of 0.024 (p 0.05). Conclusion: There is a relationship between the anxiety level of post section caesarea mothers and milk production in Ciamis General Hospital. These results prove that anxiety is one of the factors that can affect the breast milk production of breastfeeding mothers.